Isolation and Characterization of Phages Active against Paenibacillus larvae Causing American Foulbrood in Honeybees in Poland - Ewa Jończyk-Matysiak; Barbara Owczarek; Ewa Popiela; Kinga Świtała-Jeleń; Paweł Migdał; Martyna Cieślik; Norbert Łodej; Dominika Kula; Joanna Neuberg; Katarzyna Hodyra-Stefaniak; Marta Kaszowska; Filip Orwat; et al. (Viruses, 2021)
The aim of this study was the isolation and characterization, including the phage effect on honeybees in laboratory conditions, of phages active against Paenibacillus larvae, the causative agent of American Foulbrood—a highly infective and easily spreading disease occurring in honeybee larva, and subsequently the development of a preparation to prevent and treat this dangerous disease. From the tested material (over 2500 samples) 35 Paenibacillus spp. strains were obtained and used to search for phages. Five phages specific to Paenibacillus were isolated and characterized (ultrastructure, morphology, biological properties, storage stability, and genome sequence). The characteristics were performed to obtain knowledge of their lytic potential and compose the final phage cocktail with high antibacterial potential and intended use of future field application. Preliminary safety studies have also been carried out on healthy bees, which suggest that the phage preparation administered is harmless.